Behavior Space-Temporal of Biofilters Based on Hazelnut Shells/Sawdust Treating Pharmaceutical and Personal Care Products from Domestic Wastewater - Villamar-Ayala, C (Elsevier B.V., 2025)
Nature-based solutions (NBS) such as biofiltration are an efficient, eco-friendly, and economical alternative for wastewater treatment under decentralized contexts. However, the influence on removing emerging contaminants (pharmaceuticals and personal care products or PPCPs), considering different typologies and seasonality fate, has been little studied. In this work, four lab-scale biofiltration typologies (BM: Biofilter + microorganisms, BEM: Biofilter + earthworms + microorganisms, BH: Biofilter + microorganisms + plants + earthworms or Biofilter hybrid, BPM: Biofilter + plants + microorganisms) were monitored seasonally (April–December, 250 days), being fed with rural domestic wastewater. Zantedeschia aethiopica (L.) and Eisenia foetida Savigny were used as biotic components, interacting with organic support components (hazelnut shells and sawdust) for removal of organic matter, nutrients, and 4 PPCPs (caffeine, ibuprofen, losartan, and triclosan). The mass balance of PPCPs was carried out considering the input (influent), output (effluent), support (soil), and plant (root and stem/leaf). The results showed that the different evaluated typologies removed close to 100 % COD, up to 89 % NH4+−N, and up to 99 % coliforms. Meanwhile, caffeine, ibuprofen, losartan, and triclosan were removed between 34 and 100 %. Seasonality or biofiltration typology was non-significantly influential (p > 0.05). However, biofilter hybrid and the warm season were the most efficient for removing organic matter, nutrients, coliforms, and PPCPs. The PPCPs fate was plants/substrate/effluent with values up to 36, 95, and 64 %, respectively. The effluent was caffeine s main fate. Substrate was the main fate of ibuprofen, losartan, and triclosan. Plants uptake caffeine as a carbon source. © 2025 Elsevier B.V.